The Determinant of Craftsmen Business Performance During Pandemic Period in Lake Toba - Diki Febrianto Marbun; Ngatno Ngatno; Andi Wijayanto (Gema Wiralodra, 2023)
This study was conducted to examine the effect of entrepreneur orientation on business performance and Innovation. This research was carried out in the Lake Toba area. The sample in this study amounted to 75 ulos craftsmen. The data collection method used a questionnaire. The analytical method used in this study is SEM with Smart PLS 3.3.3. The results of this study indicate that entrepreneur orientation does not have a significant influence on business performance. Innovation can mediate the influence of Entrepreneur Orientation on Business Performance.